2017
DOI: 10.1097/gox.0000000000001516
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms among Plastic Surgery Residents

Abstract: Background:A literature review did not reveal any study investigating the prevalence of depression among plastic surgery residents.Methods:We conducted a cross-sectional mail survey and included all Saudi Plastic Surgery residents in our local program in Saudi Arabia. The Beck Depression Inventory II was used.Results:The inventory showed that mild, moderate, and severe depressive symptoms were prevalent in 20.6%, 38.2%, and 11.8%, respectively. Junior residents were more prone to depression.Conclusions:The hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
3
1
Order By: Relevance
“…In comparison to the other local studies on depression found among residents, 8 , 9 , 10 our study found an even higher prevalence of depressive symptoms, with approximately 93% of the residents screening positive in the PHQ-2 questionnaire. We believe the difference in findings is due to the instrument used to estimate the prevalence of depression.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…In comparison to the other local studies on depression found among residents, 8 , 9 , 10 our study found an even higher prevalence of depressive symptoms, with approximately 93% of the residents screening positive in the PHQ-2 questionnaire. We believe the difference in findings is due to the instrument used to estimate the prevalence of depression.…”
Section: Discussioncontrasting
confidence: 84%
“…While a recent study from Oman found higher prevalence of depression among the female residents, 21 the findings of other local studies have demonstrated conflicting association. 8 , 9 , 10 In a systematic review of the prevalence of depression and depressive symptoms found among the resident physicians, no clear associations were found between the non-surgical and surgical residents, and junior versus senior residents. 4 In our study, the residents training in the larger tertiary care centre (King Abdulaziz Medical City) reported higher depressive symptoms than the residents of the two smaller hospitals in the Qassim region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although burnout among several surgical specialties has been investigated, burnout among plastic surgery residents in Saudi Arabia is only being started to be evaluated, and a study investigating depressive symptoms among plastic surgery residents in Saudi Arabia 11 has reported depressive symptoms rates of 70.6%.…”
Section: Introductionmentioning
confidence: 99%